The effect of scientific evidence on conservation practitioners' management decisions - Walsh, Jessica C (Conservation biology : the journal of the Society for Conservation Biology, 2015)
© 2014 The Authors. Conservation Biology published by Wiley Periodicals, Inc. on behalf of Society for Conservation Biology.